Effects of reconstituted HDL on charge-based LDL subfractions as characterized by capillary isotachophoresis - Zhang Bo; Uehara Yoshinari; Hida Satoru; Miura Shin-ichiro; David L. Rainwater; Segawa Masaru; Kumagai Koichiro; Rye Kerry-Anne; Saku Keijiro (Journal of Lipid Research, 2007)
Modified LDL in human plasma including small, dense LDL (sdLDL) and oxidized LDL carries a more negative charge than unmodified LDL and is atherogenic. We examined the effects of apolipoprotein A-I (apoA-I)/POPC discs on charge-based LDL subfractions as determined by capillary isotachophoresis (cITP). Three normal healthy subjects and seven patients with metabolic disorders were included in the study. LDL in human plasma was separated into two major subfractions, fast- and slow-migrating LDL (fLDL and sLDL), by cITP. Normal LDL was characterized by low fLDL, and mildly oxidized LDL in vitro and mildly modified LDL in human plasma were characterized by increased fLDL. Moderately oxidized LDL in vitro and moderately modified LDL in a patient with hypertriglyceridemia and HDL deficiency were characterized by both increased fLDL and a new LDL subfraction with a faster mobility than fLDL [very-fast-migrating LDL as determined by cITP (vfLDL)]. cITP LDL subfractions with faster electrophoretic mobility (fLDL vs. sLDL, vfLDL vs. fLDL) were associated with an increased content of sdLDL. Incubation of a plasma fraction with d > 1.019 g/ml (depleted of triglyceride-rich lipoproteins) in the presence of apoA-I/POPC discs at 37°C greatly decreased vfLDL and fLDL but increased sLDL. Incubation of whole plasma from patients with an altered distribution of cITP LDL subfractions in the presence of apoA-I/POPC discs also greatly decreased fLDL but increased sLDL. ApoA-I/POPC discs decreased the cITP fLDL level, the free cholesterol concentration, and platelet-activating factor acetylhydrolase activity in the sdLDL subclasses (d = 1.040–1.063 g/ml) and increased the size of LDL. ApoA-I/POPC discs reduced charge-modified LDL in human plasma by remodeling cITP fLDL into sLDL subfractions.